Órteses para o pé com cunha medial alteram a cinemática do retropé, tíbia e fêmur em corredores com dor femoropatelar: uma análise usando statistical parametric mapping - Silva, Hygor Ferreira (Universidade Federal de São Carlos, 2024)
Medially wedged foot orthoses are recommended for short-term pain reduction in individuals with patellofemoral pain (PFP). However, the precise mechanism underlying pain reduction remains unclear. Inconsistencies exist in the literature regarding the effects of these orthoses on lower limb kinematics during running in individuals with PFP. An important limitation of prior studies assessing the effects of medially wedged foot orthoses on lower limb kinematics in this population is the use of discrete parameters for movement analysis, which may not offer a comprehensive description of observed movement patterns. Statistical Parametric Mapping (SPM) presents an alternative approach, capable of identifying differences across the entire time series, thus offering a more robust motion analysis technique. The primary aim of this study was to investigate the immediate effects of employing medially wedged foot orthoses on the kinematics of the rearfoot, tibia, and femur during the stance phase of running in individuals with PFP, utilizing SPM. A secondary aim was to evaluate the immediate effects of this orthoses on pain intensity and self-perception of improvement or worsening. This study employed a randomized crossover design involving 30 runners with PFP (mean age 29.7 ± 5.3 years) exhibiting excessive subtalar pronation. Participants underwent two test conditions: 1) a control condition involving the use of running shoes with original insoles, and 2) an intervention condition utilizing a 3/4 foot orthoses with a 4° medial wedge. A three-dimensional kinematic analysis during treadmill running was recorded, and the variables of interest were the movement of the rearfoot in the frontal plane, and the movement of the tibia and femur in the frontal and transverse planes. Pain intensity and self-perception of improvement or worsening were assessed using the Visual Analog Scale and the Global Rating of Change scale, respectively. The use of the medially wedged foot orthoses resulted in reduced rearfoot eversion (18-81% of the stance phase) (p=0.007), increased tibial medial rotation at the beginning of the stance phase (0-24%; p=0.004), but a reduction in this movement between 40 and 84% of the stance phase (p <0.001). Furthermore, the orthoses induced an increase in femoral medial rotation at the beginning of the stance phase (0-5%; p=0.043) and femoral adduction between 23-47% of the stance phase (p=0.011). Despite not yielding a reduction in pain intensity (p=0.940), the orthoses led to a significantly greater self-perceived improvement (p=0.031). In conclusion, the use of a 4° medially wedged foot orthoses demonstrated the capacity to modify lower limb kinematics in runners with PFP, resulting in higher self-perception of improvement.
Foot orthoses with medial wedge alter the kinematics of the rearfoot, tibia and femur in runners with patellofemoral pain: an analysis using statistical parametric mapping
Keywords: Running; Biomechanics; Patellofemoral pain; Foot orthoses; Corrida; Biomecânica; Dor femoropatelar; Palmilha; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL